The Role of Emotional Intelligence (EQ) in Improving the Quality of Teacher-Student Interaction: A Review of Educational Psychology Literature - Rian sukawati; Jaenullah, Jaenullah; Dedi Setiawan (Journal of Research in Islamic Education, 2024)
This study aims to thoroughly reveal the role of emotional intelligence (EQ) in improving the quality of teacher-student interactions. Teachers' emotional intelligence (EQ) is considered an important aspect in facilitating meaningful interactions for students. This study includes a literature study (Library Research). Data collection identifies sources relevant to the research conducted through online database searches (Scopus, Google Scholar, National Library) and offline (relevant books and documents) then the relevant data is analyzed comprehensively and systematically. The research findings indicate that teachers with high EQ are better able to create a positive classroom environment, build supportive relationships with students, and manage conflict effectively. EQ teachers also increase student learning motivation, academic engagement, and academic achievement. This review emphasizes the important role of EQ in improving the quality of student-teacher interactions. It is recommended to integrate EQ aspects into teacher training programs and develop valid EQ assessment tools, as well as explore teaching strategies that integrate EQ with other pedagogical approaches.